THE INFLUENCE OF FINANCIAL LITERACY, PARENTS' SOCIO-ECONOMIC STATUS, AND LIFESTYLE ON CONSUMPTIVE BEHAVIOR OF ADOLESCENTS - Muh Fahrurrozi; Muhammad Rapii; Baiq Intan Baiq Intan Fuji (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
Consumptive behavior of adolescents causes them not to thought long in bought things that were not really needed. The aim of this study was to find out (1) the consumptive behavior of junior high school students, and (2) the influence of financial literacy, socio economics, and lifestyle on the consumptive behavior of junior high school adolescents. Where this research uses a quantitative approach with the ex post facto method with a total sample of 36 students. Collecting data using tests, questionnaires and documentation and questionnaires. Data analysis used multiple linear regression. The results of the descriptive analysis showed that the level of adolescent consumptive behavior was 64% having moderate consumptive behavior, 22% adolescents having consumptive behavior in the high category, and 14% in the low category. The results showed that there was a significant influence between financial literacy, socioeconomic and lifestyle on consumptive behavior